RELATIVE ABUNDANCE AND DISTRIBUTION OF ADULT SPECIES OF THE ANOPHELES GAMBIAE COMPLEX IN UNIVERSITY OF ABUJA STAFF QUARTERS, GIRI ABUJA FCT, NIGERIA - Madara, A. A.; Ebuzoeme, V. (FUDMA Journal of Sciences, 2023)
A study on the distribution and abundance of Anopheles mosquito species was carried out in University of Abuja staff Quarters Giri, Nigeria. A total of 848 adult mosquitoes were collected. Sampling of mosquitoes performed using various methods: pyrethrum spray catches, human baits, electric mosquito killer and larval collections. Four species were encountered namely, Anopheles gambiae, Anopheles arabiensis, Anopheles funestus and Anopheles rufipes. Anopheles arabiensis was the most abundant of the four species with 367(43.30%) followed by Anopheles gambiae 257(30.30%), Anopheles funestus 117 (13.80%) and Anopheles rufipes 107(12.60%) respectively. Of the 848 Anopheline mosquitoes, 511(63.30%) were females while 337(39.70%) were males. These results indicate that members of the anopheline Gambiae complex which are amongst the most efficient and effective human malaria vectors in Nigeria are breeding in the study area, most of which are encouraged by human activities. There is need to develop control strategies that will target the vector species.